Do CEOs with government work experience foster enterprise investment in pollution control? - Mixiang Peng; Dayuan Li; Chaolin Zhang (PLoS ONE, 2025)
As enterprise leaders, CEOs play a critical role in driving enterprise investment in pollution control. However, few studies have explored the motivations behind enterprise investment in pollution control, primarily how CEOs’ early experiences influence their decisions. Based on the perspective of imprinting theory, this study examines the impact of CEOs with government work experience on enterprise investment in pollution control and the boundary conditions of this impact. Using data from a survey of private enterprises in China from 2008 to 2014, the empirical results indicate that CEOs with government work experience are likelier to promote enterprise investment in pollution control. Additionally, a CEO’s perceptions of economic, social, and political status negatively moderate the relationship between their government work experience and enterprise investment in pollution control. This study enriches and deepens the study on career imprinting in non-commercial fields, status perception, and sustainable development and provides practical significance for hiring CEOs with government work experience to promote enterprise investment in pollution control.